Optimalisasi Peran Wanita dalam Meningkatkan Gizi dan Kesehatan Masyarakat melalui Pangan Lokal pada Kelompok Wanita Tani - Dasril, Oktariyani; Marsyah, Finy; Syukriani, Lily; Rosadi, Firsta Ninda; Sary, Annisa Novita (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Local food is a strategic resource with great potential in supporting food security and improving community nutrition. However, its utilization remains limited due to the low knowledge and skills of the community in processing local food into nutritious and economically valuable products. This community service activity is carried out by lecturers and students of Syedza Saint University in the Air Tawar Timur sub-district, North Padang, in partnership with the Women's Farmers Group (KWT) Berseri. Purpose: The goal of the activity is to improve knowledge, skills, and economic independence of the community through nutrition education, training in processing local food, packaging, and marketing products. The implementation method includes socialization, counseling, hands-on training, and assistance in production and marketing. Evaluation was conducted using pre-test and post-test assessments, as well as product quality evaluation. Result: The results showed a significant increase in participants' knowledge, from an average of 53% in the pre-test to 89% in the post-test. Participants also successfully produced innovative products based on local ingredients, such as moringa cookies, sweet potato muffins, healthy banana chips, and nutritious child snacks, which received positive feedback from consumers. This activity has a tangible impact, resulting in increased nutritional knowledge, changes in consumption behavior at the household level, and the opening of small business opportunities based on local food, managed by women farmers. Thus, this program has proven to be effective in supporting family nutrition improvement, women's economic empowerment, and the utilization of local food potential as an effort towards sustainable food security. Keywords: Women's Farmer Group, Nutrition, Local Food, Community Empowerment, Entrepreneurship.  ABSTRAK  Pangan lokal merupakan sumber daya strategis yang berpotensi besar dalam mendukung ketahanan pangan serta peningkatan gizi masyarakat. Namun, pemanfaatannya masih terbatas karena rendahnya pengetahuan dan keterampilan masyarakat dalam mengolah pangan lokal menjadi produk yang bergizi dan bernilai ekonomis. Kegiatan pengabdian kepada masyarakat ini dilaksanakan oleh dosen dan mahasiswa Universitas Syedza Saint di Kelurahan Air Tawar Timur, Kecamatan Padang Utara, dengan mitra Kelompok Wanita Tani (KWT) Berseri. Tujuan: Tujuan kegiatan adalah meningkatkan pengetahuan, keterampilan, dan kemandirian ekonomi masyarakat melalui edukasi gizi, pelatihan pengolahan pangan lokal, pengemasan, dan pemasaran produk. Metode pelaksanaan meliputi sosialisasi, penyuluhan, pelatihan berbasis praktik langsung, serta pendampingan dalam produksi dan pemasaran. Evaluasi dilakukan menggunakan pre-test dan post-test, serta penilaian kualitas produk. Hasil kegiatan menunjukkan adanya peningkatan signifikan pengetahuan peserta, yaitu dari rata-rata 53% pada pre-test menjadi 89% pada post-test. Peserta juga berhasil menghasilkan produk inovatif berbasis pangan lokal, seperti cookies kelor, muffin ubi, keripik pisang sehat, dan snack anak bergizi, yang mendapat respons positif dari konsumen. Kegiatan ini memberikan dampak nyata berupa peningkatan pengetahuan gizi, perubahan perilaku konsumsi di tingkat rumah tangga, serta terbukanya peluang usaha kecil berbasis pangan lokal yang dikelola oleh wanita tani. Dengan demikian, program ini terbukti efektif dalam mendukung peningkatan gizi keluarga, pemberdayaan ekonomi perempuan, dan pemanfaatan potensi pangan lokal sebagai upaya menuju ketahanan pangan berkelanjutan. Kata Kunci: Kelompok Wanita Tani, Gizi, Pangan Lokal, Pemberdayaan Masyarakat, Kewirausahaan.